STOCK MARKET REACTION TO WHO’S COVID-19 ANNOUNCEMENT IN ASEAN-5 REGION - Meryn, Felice; Imelda, Elsa (International Journal of Application on Economics and Business, 2023)
The aims of this research is to analyze the stock market reaction in the ASEAN-5 region (Indonesia, Malaysia, Singapore, Philippines, and Thailand) to the announcement of the global COVID-19 pandemic by the World Health Organization (WHO). The method used is an event study with abnormal return as the independent variable. The sample in this study is the main stock index of ASEAN-5 countries. Empirical results showed that there was a significant and insignificant abnormal return on certain days around the announcement of the COVID-19 pandemic by WHO in ASEAN-5. Subsequent findings showed that there was no difference in abnormal returns before and after the global announcement of COVID-19 by WHO.